2018
DOI: 10.1002/macp.201800421
|View full text |Cite
|
Sign up to set email alerts
|

The Swelling of Poly(Isopropylacrylamide) Near the θ Temperature: A Comparison between Linear and Cross‐Linked Chains

Abstract: Thermoresponsive polymeric gels are a class of smart materials with the ability to absorb or release large amounts of solvent when changes in their environment occur. Scaling theories of gel swelling (de Gennes' c∗ theorem and Obukhov's model) predict that the swelling of a gel correlates with that of a linear chain with equal degree of polymerization to that of a network strand. Data on linear and cross‐linked poly(N‐isopropylacrylamide) (PNIPAM) in aqueous solutions of different molar masses under θ temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 122 publications
1
16
0
Order By: Relevance
“…This can be considered as a lower estimate of σ, according to different types of measurements for linear PNIPAM chains. 44 Note that the use of a larger value of σ would significantly decrease λ B , thus resulting in a very small effect of the Debye-Hückel repulsion as compared to the neutral case.…”
Section: Monomer Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be considered as a lower estimate of σ, according to different types of measurements for linear PNIPAM chains. 44 Note that the use of a larger value of σ would significantly decrease λ B , thus resulting in a very small effect of the Debye-Hückel repulsion as compared to the neutral case.…”
Section: Monomer Interactionsmentioning
confidence: 99%
“…Kuhn length of both neutral NIPAM and charged AAc monomers. This can be considered as a lower estimate of σ, according to different types of measurements for linear PNIPAM chains 44. …”
mentioning
confidence: 99%
“…Since the NIPAAm and NAPMAm monomers have roughly the same backbone length of l ≈ 0.25 nm, we can estimate the strand size in a gel composed of these monomers using the Kuhn length l k found in linear poly­(isopropylacrylamide) (PNIPAM) in aqueous solution. Recently, Lopez et al reported an estimated Kuhn length l k ≈ 4 ± 1 nm for linear PNIPAM by fitting static and dynamic light scattering (SLS/DLS) data on the chain hydrodynamic radius and R g to the ideal worm-like chain model, while previous single-molecule force spectroscopy (SMFS) experiments rendered a much smaller average value of l k ≈ 0.7 nm, see ref and references therein. Taking the SLS/DLS value of l k ≈ 4 nm, there are l k / l ≈ 16 NIPAAm monomers per Kuhn segment in a linear PNIPAM.…”
Section: Resultsmentioning
confidence: 99%
“…In the 20% gel samples we used, the average number of 36.25 NIPAAm/NAPMAm monomers per strand corresponds to N k ≈ 2.26 Kuhn segments. The average network strand sizes in the absence of Ru­(bpy) 3 groups can then be estimated as R e ≈ N k 1/2 l k ≈ 6.02 nm and R g ≈ 2.46 nm using the Gaussian chain model and R e ≈ 5.32 nm and R g ≈ 1.85 nm using the ideal worm-like chain model. , If the SMFS value of l k ≈ 0.7 nm is used instead, each strand would have N k ≈ 12.95 Kuhn segments, giving estimated strand sizes R e ≈ 2.52 nm and R g ≈ 1.03 nm using the Gaussian chain model and R e ≈ 2.47 nm and R g ≈ 0.97 nm using the ideal worm-like chain model. On the other hand, the Ru­(bpy) 3 complex takes a spherical shape with an estimated diameter of approximately 1.3 nm, which is of comparable order to the gel strand size.…”
Section: Resultsmentioning
confidence: 99%
“…58 In all cases, increasing temperature results in a significant decrease in the liquid viscosity since it reduces the particle size. 59 In this work, we deal with small linear PNIPAM microgels in comparatively low solution concentrations. Their viscosity does not change substantially as a function of the shear rate, and the assumption of being a Newtonian liquid may be valid (Figure S17 in the Supporting Information).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%